Pengaruh Pendampingan Lembaga Swadaya Masyarakat Obor Tani Terhadap Kompetensi Petani Durian di Desa Lerep Kabupaten Semarang - Rastradinar, Karin Mega; Gayatri, Siwi; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Durian is one of the main commodities produced in Lerep Village, Semarang Regency. Farmers' competence influences their level of awareness and understanding in cultivating durian plants. This competence is closely related to the role of non-governmental organizations (NGOs), which act as motivators, dynamizers, and facilitators. This study aims to analyze the influence of assistance provided by the NGO Obor Tani as a motivator, dynamizer, and facilitator on the competence of durian farmers in Lerep Village, Semarang Regency. The research was conducted from October to December 2024 in Lerep Village, Semarang Regency. The location was selected purposively based on the consideration that durian farmers in Lerep Village have received assistance from the NGO Obor Tani. The research method used is a survey, selected due to its suitability in collecting information from a relatively small number of individuals who are representative of the population in this case, durian farmers in Lerep Village. The sampling method applied is probability sampling, specifically simple random sampling. The sample size was determined using the Slovin formula, resulting in a total of 72 respondents. Data collection was carried out through interviews using questionnaires and field observations. The data were analyzed using multiple linear regression analysis. Based on the results of the regression analysis, the roles of Obor Tani as a motivator, dynamizer, and facilitator simultaneously have a significant effect on the competence of durian farmers in Lerep Village. Furthermore, partially, each role of Obor Tani both as a motivator, dynamizer, and facilitator also has a significant effect on the competence of durian farmers in Lerep Village.